2010
DOI: 10.1007/s11033-010-0215-y
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of Solanum nigrum: can networks help?

Abstract: Black nightshades are a group of species best known for their 'poisonous' or noxious weedy reputation. It is not so well known that species of this group serve as emerging food source in many countries worldwide especially in the African continent. Despite the fact that the section has recently been studied extensively, taxonomy is still unsettled and debated because of inter- and intraspecific hybridization, phenotypic plasticity and polyploidization. In this study we analyze the genetic relationships among d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 101 publications
(108 reference statements)
2
32
0
Order By: Relevance
“…It also plays an important role as a model plant. Potato (Solanum tuberosum L.), tomato (Solanum lycopersicum L.) (Poczai and Hyvönen 2011;Edmonds and Chweya 1997), and eggplant (Solanum melongena L.) are examples of this family. Tomato is the most popular and commonly cultivated seasonal vegetable crop worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…It also plays an important role as a model plant. Potato (Solanum tuberosum L.), tomato (Solanum lycopersicum L.) (Poczai and Hyvönen 2011;Edmonds and Chweya 1997), and eggplant (Solanum melongena L.) are examples of this family. Tomato is the most popular and commonly cultivated seasonal vegetable crop worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Poczai and Hyvönen (2011) [48] applied ISSR markers combined with start codon targeted polymorphisms (SCoT) and chloroplast sequence data as well as morphological traits to analyse the genetic relationship among diploid, tetraploid and hexaploid Solanum species of the S. nigrum complex. They found out that all the accessions of the diploid species shared a cluster with all the polyploid species, and concluded that the polyploid species have originated in few combinations of genetically differentiated diploids.…”
Section: Inter-simple Sequence Repeats (Issrs)mentioning
confidence: 99%
“…Split networks must be viewed in a more abstract way as they give a visual representation of incompatible signals in certain parts of phylogeny (Huson and Steel 2004). They also generate high portion of false negative results and for this reason the results should be handled with substantial caution (Bell and Hyvönen 2010;Poczai and Hyvönen 2011). Contrary to split NNets, recombination networks can be interpreted directly.…”
Section: Morphological Traitmentioning
confidence: 99%